Learn Japanese (Nihongo) : - Akiyama, Nobuo (Barron’s, 1990)
Here's how to learn Japanese painlessly for vacationing, shopping, making phone calls, dining, sightseeing, and generally getting around Japanese cities and countrysides. Vocabulary cards, gummed labels and other fun-learning features come as part of the book.